2010
DOI: 10.1111/j.1365-2249.2010.04140.x
|View full text |Cite
|
Sign up to set email alerts
|

An imbalance in mucosal cytokine profile causes transient intestinal inflammation following an animal's first exposure to faecal bacteria and antigens

Abstract: SummaryIntestinal microflora play a critical role in the initiation and perpetuation of chronic inflammatory bowel diseases. In genetically susceptible hosts, bacterial colonization results in rapid-onset chronic intestinal inflammation. Nevertheless, the intestinal and systemic immune response to faecal bacteria and antigen exposure into a sterile intestinal lumen of a post-weaned animal with a mature immune system are not understood clearly. This study examined the effects of faecal bacteria and antigen expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The consortium of resident enteric bacteria provides protective signals to host immune defenses (40)(41)(42). Colonization of GF WT mice with resident fecal microbiota rapidly stimulated mucosal proinflammatory cytokine production manifested by transient release of TNF-α, IL-12p40, and IFN-γ, but not IL-17a, within 3 days, while intestinal IL-10 levels gradually increased to maximum sustained levels in 7 days (43). The finding that transient in vivo stimulation of proinflammatory cytokine gene expression was followed by downregulation to basal levels in ex-GF Il10 +/+ but not in Il10 -/mice advances the hypothesis that resident microbiota induces IL-10 production by LP immune cells that mediates mucosal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The consortium of resident enteric bacteria provides protective signals to host immune defenses (40)(41)(42). Colonization of GF WT mice with resident fecal microbiota rapidly stimulated mucosal proinflammatory cytokine production manifested by transient release of TNF-α, IL-12p40, and IFN-γ, but not IL-17a, within 3 days, while intestinal IL-10 levels gradually increased to maximum sustained levels in 7 days (43). The finding that transient in vivo stimulation of proinflammatory cytokine gene expression was followed by downregulation to basal levels in ex-GF Il10 +/+ but not in Il10 -/mice advances the hypothesis that resident microbiota induces IL-10 production by LP immune cells that mediates mucosal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The first introduction of gut microbiota to an animal raised under axenic conditions results in a transient proinflammatory response that is replaced by an anti-inflammatory response by 7 days and is associated with inflammatory mononuclear cell infiltrates into the lamina propria (38). Effects of gut microbiota and the amount of LPS in the diet also affect the acquired immune response in the gut and draining lymphoid organs (39).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that normal wildtype mice kept in an axenic environment and then exposed to the endogenous microbiota as adults mount a transitory inflammatory immune response to the bacteria and their antigens resulting in a brief intestinal inflammation. Subsequent establishment of homeostasis appears to be an important step for tolerance induction 23…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that acquisition of the endogenous flora leads to a brief immune response to bacterial antigens that may be required for tolerance induction 22. These bacteria‐triggered immune responses can lead to transient intestinal inflammation in adult axenic mice following association with endogenous flora, due to a temporary imbalance in intestinal homeostatic cytokine release 23. Healthy wildtype mice return to a state of nonresponsiveness to bacterial antigens within 14 days; in contrast, mice with a genetic defect, such as the lack of cytokines (interleukin [IL]‐10 and IL‐2), T‐cell receptor (TCR) abnormalities (TCRα −/− ), and epithelial barrier deficiencies (mdr1a−/−) remain responsive to bacterial antigens 22, 24–28.…”
mentioning
confidence: 99%